Analisis Pengaruh Ukuran Perusahaan Dan Opini Audit Terhadap Auditor Switching Pada Sektor Industri - Nabilla Faradhillah; Dirvi Surya Abbas (Prosiding, 2022)
This study aims to analyze how the influence of company size and audit opinion on auditor switching in the industrial sector on the Indonesia Stock Exchange in 2016-2020.This research is a quantitative descriptive research. The population in this study are industrial sector companies listed on the Indonesia Stock Exchange in 2016-2020, totaling 30 samples. The conclusion of this study is that partially the Company Size and Audit Opinion have an effect on Auditor Switching in industrial sector companies on the IDX.